An Econometric Analysis of Clean Energy Supply and Industrial Development in Nigeria: Implications for Sustainable Development - Aderemi, Timothy Ayomitunde; Alejo, Abidemi; Omoyele, Olufemi Samuel; Olaoye, Olusegun Peter; Olanipekun, Wahid Damilola; Azuh, Dominic Ezinwa (International Journal of Energy Economics and Policy, 2022)
The continuous demand and usage of energy in large quantum for industrial purposes has motivated the global advocacy for energy sustainability (SDG-7). Against this backdrop, this study employed various econometric techniques to study the nexus between clean energy supply in Nigeria and industrial development between 1990 and 2019. This study sets to establish the nature of the relationship in the long run, direction of causality and the stochastic dynamic interaction between clean energy supply and industrial development in Nigeria. Consequently, the following findings emerged from this study; clean energy supply and manufacturing value added had a significant negative relationship. This implies that the contribution of clean energy supply is negatively significant to the manufacturing value added in the Country. Therefore, the supply of electricity production from hydroelectric sources had not led to industrial development in Nigeria. Further evidence indicates that no feedback relationship exists between clean energy supply and industrial development. Also, the stochastic dynamic interaction between clean energy supply and industrial development shows a shock to manufacturing value added determines the behavior of clean energy supply to a larger extent in one hand, whereas, variance decomposition of clean energy supply shows the similar effect on the behavior of industrial development on the other hand. In the light of the findings from this study, the following recommendations are made for the policymakers in Nigeria; in achieving the Sustainable Development Goal (SDG 7), clean energy supply could be explored for future industrial development in Nigeria, thought it currently lacks the capacity to drive the manufacturing sector of the economy. And as such, the Nigerian policymakers and other stakeholders should work hard to achieve sustainable supply of adequate electricity production from hydroelectric sources in the country.